Minimum Wage Analysis Using a Pre-Committed Research Design: Evidence through 2016 - Jeffrey Clemens; Michael R. Strain (Institute of Labor Economics (IZA), 2018)
This paper presents results from the first year of a multi-year, pre-committed research design for analyzing recent state-level minimum wage changes. Through 2015 and 2016, we estimate that relatively large statutory minimum wage increases have reduced employment among low-skilled population groups by just under 1.5 percentage points. Our estimates of the effects of smaller minimum wage increases are more variable and include both moderately large positive values and modest negative values. Our estimates of the effects of increases linked to inflation-indexing provisions are also quite variable, taking a small positive value on average across specifications. Results including 2016 diverge nontrivially when we compare estimates using the American Community Survey (ACS) to estimates using the Current Population Survey (CPS), with estimates tending to be more negative in the ACS. Analysis of future data will be needed to determine whether this difference across surveys is most appropriately attributed to sampling variations or to some other cause.
Keywords: J08; J23; J38; 330; minimum wages; employment; pre-commitment